Adaptive empathic response selection is sensitive to multiple dimensions of social interaction - Elena Kozakevich Arbel; Simone G. Shamay-Tsoory; Uri Hertz (Communications Psychology)
Abstract During empathic response selection, individuals draw from both past experiences and social cues, including the distressed person’s identity, their emotional state, and the cause of distress. To study how these social dimensions influence empathic-response learning we integrated a multidimensional learning paradigm, computational modelling, and adaptive empathy framework. Participants identified effective empathic responses across two blocks of distress scenarios, with one social dimension altered between blocks. We anticipated two learning patterns: dimension-sensitive, treating each change as a new learning experience, and dimension-insensitive, relying on previous experience as a baseline. We found that participants were sensitive to changes in person, emotional state, and distress cause, but to different degree. The person dimension was the most salient, suggesting that the distressed person’s identity is the primary reference point when interacting with others. Our findings provide a quantitative evaluation of the weight given to different dimensions of social interactions, which may help understand how people perceive and react in such scenarios.